Carbonic anhydrases from Trypanosoma cruzi and Leishmania donovani chagasi are inhibited by benzoxaboroles. (1st January 2018) - Nocentini, Alessio; Cadoni, Roberta; Dumy, Pascal; Supuran, Claudiu T.; Winum, Jean-Yves
Abstract: A series of 6-substituted ureido- and thioureido-benzoxaboroles were investigated as inhibitors of carbonic anhydrases from Trypanosoma cruzi (TcCA), and Leishmania donovani chagasi (LdcCA). Both enzymes were inhibited by benzoxaboroles in the micromolar range. Preferential inhibitory potency against the β-CA LdcCA versus the α-CA TcCA was observed with submicromolar inhibitory activities. Some derivatives displayed excellent inhibitory and selectivity profile over the ubiquitous and physiological relevant human off-target hCA II. This study provides a convincing opportunity to study benzoxaborole scaffold for the design of antiprotozoan potential drugs targeting the pathogen's carbonic anhydrases.